Workshop dan Pendampingan Pembuatan Sitasi dan Referensi Berbasis Aplikasi bagi Mahasiswa Senior PSP Bahasa Inggris FKIP Universitas Mataram - Sujana, I Made; Saputra, Agus; Fitriana, Eka; Alfin Haris Munandar, La Ode; Pasaribu, Beta Rida; Wulandari, Ayunda; Sumarti, Siti (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
One of the challenges faced by students in writing scientific publications is how to properly conduct citation and referencing. Most students still rely on traditional methods. With the rapid development of technology, various applications have been created to simplify citation and reference management. This activity aims to provide knowledge and skills in utilizing Mendeley and Zotero to generate citations and references automatically. The program was carried out through interactive lectures and hands-on assistance in using digital applications for citation and reference creation. It involved 34 seventh-semester students of the English Education Study Program, FKIP, University of Mataram, facilitated by English lecturers. The materials presented included the role of citations and references in scientific writing, installation of Mendeley and Zotero, data input practice, and training on generating automatic citations and references. Survey results show that the activity was well-implemented and aligned with the plan. All participants (100%) gained knowledge about the use of Mendeley and Zotero, almost all participants (96.8%) successfully installed both applications, and 89.9% felt confident that they would be able to apply these tools in their future academic writing tasks. Responses from the open-ended questions also indicated positive feedback from the participants.